A Didactics of Cultural Readings - Jensen, Mikkel (Teaching and Learning Inquiry, 2023)
This article makes a case for the effectiveness of using imitation-style teaching as a way to introduce how to write theoretically informed pieces of literary or media criticism to undergraduates. By making a case for the relevance of teaching this form of criticism in the undergraduate classroom, as well as exploring exactly how imitation-style teaching can be used to teach this skill, this article argues that teachers can fruitfully study closely with students pieces of literary criticism in the undergraduate classroom. The article argues that this teaching practice is able to live up to the idea of “transparent performance expectations,” one of didactician Hilbert Meyer’s 10 central criteria for good teaching. Click here to read the corresponding ISSOTL blog post.